1998
DOI: 10.3928/1081-597x-19980701-05
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Aberrations and Visual Performance After Radial Keratotomy

Abstract: BACKGROUND: Refractive surgery and videokeratography have allowed us to study the effects on visual performance of relatively large changes in corneal aberration structure induced by surgical changes in corneal shape. METHODS: We quantified in one eye of nine normal and 23 radial keratotomy patients, the area under the log contrast sensitivity function (AULCSF) and corneal first surface wavefront variance for two artificial pupil sizes (3 and 7 mm). Contrast sensitivity was measured with sine-wave gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
122
0
4

Year Published

1998
1998
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 265 publications
(132 citation statements)
references
References 32 publications
4
122
0
4
Order By: Relevance
“…PRK, 4,11,12 similarly to after RK 5,13 and LASIK. 10,11,[14][15][16] Applegate et al 5 reported that the area under the contrast sensitivity function decreases as the wavefront variances increase after RK.…”
mentioning
confidence: 77%
See 2 more Smart Citations
“…PRK, 4,11,12 similarly to after RK 5,13 and LASIK. 10,11,[14][15][16] Applegate et al 5 reported that the area under the contrast sensitivity function decreases as the wavefront variances increase after RK.…”
mentioning
confidence: 77%
“…The area under the log contrast sensitivity function (AULCSF) was calculated from the data obtained with the CSV-1000E sine wave grading chart. AULCSF was determined according to the method of Applegate et al 5 The log of contrast sensitivity was plotted as a function of log spatial frequency, and thirdorder polynomials were fi tted to the data. The fi tted function was integrated between the fi xed limits of log spatial frequency of 0.48 (corresponding to 3 cpd) and 1.26 (18 cpd), and the resulting value was defi ned as the AULCSF.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The contrast level of the last correct response for each cpd was recorded as the contrast threshold in logarithmic value under full spectacle correction. We then calculated the area under the log contrast sensitivity function (AULCSF) as representative of the contrast sensitivity data according to the method of Applegate et al [41]. The log contrast sensitivity versus log spatial frequency data were fitted to a third-order polynomial curve.…”
Section: Ophthalmic Examinationsmentioning
confidence: 99%
“…Contrast sensitivity function under the photopic condition was evaluated with best-spectacle correction at 3, 6, 12, and 18 cycles per degree (c/d) using the CSV-1000E chart (Vector Vision Co., Greenville, OH), and the area under the log contrast sensitivity function (AULCSF) was calculated according to the method of Applegate et al [14]. In brief, the log of contrast sensitivity was plotted as a function of log spatial frequency, and third-order polynomials were fitted to the data.…”
Section: Measurementsmentioning
confidence: 99%